2018
DOI: 10.1016/j.ypmed.2018.03.022
|View full text |Cite
|
Sign up to set email alerts
|

The carry-over effects of school gardens on fruit and vegetable availability at home: A randomized controlled trial with low-income elementary schools

Abstract: This group-randomized controlled trial examines the effects of a school garden intervention on availability of fruits and vegetables (FV) in elementary school children's homes. Within each region, low income U.S. schools in Arkansas, Iowa, New York, and Washington State were randomly assigned to intervention group (n = 24) or waitlist control group (n = 22). Children were in grades 2, 4, and 5 at baseline (n = 2768). The garden intervention consisted of both raised-bed garden kits and a series of grade-appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…Previous studies have found a positive link between active-PEB and people's general health (Soga, Gaston, & Yamaura, 2017), connectedness to nature (Whitburn et al, 2018), physical activity (Wells, Myers, & Henderson, 2014), healthy diet (Wells et al, 2018), environmental knowledge (Lewandowski & Oberhauser, 2017) and other PEB like water and energy savings (Markle, 2013). Taken together, these findings suggest that active-PEB play a unique role in increasing people's OPA, health, and nature conservation.…”
Section: Positive Effects Of Land Stewardship Behavioursmentioning
confidence: 67%
See 1 more Smart Citation
“…Previous studies have found a positive link between active-PEB and people's general health (Soga, Gaston, & Yamaura, 2017), connectedness to nature (Whitburn et al, 2018), physical activity (Wells, Myers, & Henderson, 2014), healthy diet (Wells et al, 2018), environmental knowledge (Lewandowski & Oberhauser, 2017) and other PEB like water and energy savings (Markle, 2013). Taken together, these findings suggest that active-PEB play a unique role in increasing people's OPA, health, and nature conservation.…”
Section: Positive Effects Of Land Stewardship Behavioursmentioning
confidence: 67%
“…Finally, policy makers could boost people's engagement on active-PEB by, for instance, increasing neighbourhood walkability (Corseuil Giehl, Hallal, Brownson, & D'Orsi, 2017) and cycling lanes (Kienteka, De Camargo, Fermino, & Reis, 2018), and improving the quality of public transportation (She et al, 2017). In turn, the promotion of land stewardship behaviours seems plausible through applied research and projects such as the ones conducted by the Institute Earthwatch (e.g., nature expeditions), tree planting (Whitburn et al, 2018), community and school gardens (Cabral et al, 2017;Wells et al, 2018Wells et al, , 2014.…”
Section: Positive Effects Of Land Stewardship Behavioursmentioning
confidence: 99%
“…In a previous study, as 304 students predominately Hispanic/Latino third-through fifth-grade in elementary school were randomly assigned to either the LA Sprouts group (nutrition, cooking, and gardening intervention) or control group, a number of determinants of dietary behaviors such as identification of vegetables and nutrition and gardening knowledge for LA Sprouts group has positively changed after the program [20]. Wells et al [21] reported that the gardening program with nutrition and environment education improved fruit and vegetable availability of 2768 students in grades second through fifth. In the United States, the 'Farm to School' has shown positive results such as increased participation in school meals, increased choice, preference, and intake of fruits and vegetables, while conducting various activities for promoting, procuring, providing, and educating local foods in schools [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, research consistently has shown that when healthier foods, such as fruits and vegetables, are available and accessible for purchase by a household and are available and accessible in the home, children have increased intake of vegetables [74][75][76][77]. A study by Wells et al (2018), found that there were carry-over effects of school gardens on vegetable availability within the home of younger children [78]. Participation in school garden programs such as TX Sprouts may have an impact beyond the school environment and may carry-over into the home environment.…”
Section: Discussionmentioning
confidence: 99%